Perlindungan Nasabah Dalam Perbankan Syariah Dan Perbankan Konvensional - Supitayanti Supitayanti; Ahmad Noor Afifudin; Tyas BS Ambarwati; Muhammad Auliya Elhakim; Luthfiyah Luthfiyah (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2024)
This research aims to analyze customer protection in sharia banking and conventional banking. This research includes descriptive qualitative research in the nature of library research. Literature sources used in this research include academic textbooks, scientific journals, research articles related to sharia banking and conventional banking. The results of this research show that: 1) Sharia banking operates with Islamic sharia principles, placing special emphasis on the concepts of justice, transparency and loss prevention for customers; 2) Conventional banking focuses on interest and profitability systems. Although both have the main goal of protecting customer assets, the methods and approaches they use differ significantly. This research describes the key aspects of both systems, examines the principles underlying them, and provides insight into how they offer protection to customers' assets. This study is important to carry out in order to add to the study of sharia banking and conventional banking, especially the scarcity of themes that discuss banking.